2015
DOI: 10.1016/j.cmi.2014.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Shift in serotype distribution of Shigella species in China, 2003–2013

Abstract: We identified 2912 Shigella isolates from diarrhoeal patients in China during 2003-2013. The most common species was Shigella flexneri (55.3%), followed by Shigella sonnei (44.1%); however, S. sonnei is becoming increasingly prevalent. Among the S. flexneri isolates, serotypes 2a and X variant (-:7,8, E1037) were the two most prevalent serotypes, and serologically atypical isolates were also commonly identified. Overall, S. sonnei, S. flexneri 2a and S. flexneri X variant (-:7,8, E1037) accounted for 76.1% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…Recent epidemiological studies conducted around the world have discovered a rise in the proportion of S. sonnei isolates compared to S. flexneri . The expansion of S. sonnei can clearly be observed from clinical surveillance studies conducted in China which show the proportion of S. sonnei isolates increasing from 17.4% in 2003–2004 to 58.2% less than a decade later, closely following the rapid industrialization in China (Figure 2 ; Mao et al, 2013 ; Qiu et al, 2015 ). Noticeably, regions that had undergone significant industrialization reported decreases in S. flexneri and increasing cases of S. sonnei compared to under developed areas where flexneri levels remain high (Qiu et al, 2015 ).…”
Section: Shigella Diversity: Epidemiology Geographical Distributionmentioning
confidence: 99%
“…Recent epidemiological studies conducted around the world have discovered a rise in the proportion of S. sonnei isolates compared to S. flexneri . The expansion of S. sonnei can clearly be observed from clinical surveillance studies conducted in China which show the proportion of S. sonnei isolates increasing from 17.4% in 2003–2004 to 58.2% less than a decade later, closely following the rapid industrialization in China (Figure 2 ; Mao et al, 2013 ; Qiu et al, 2015 ). Noticeably, regions that had undergone significant industrialization reported decreases in S. flexneri and increasing cases of S. sonnei compared to under developed areas where flexneri levels remain high (Qiu et al, 2015 ).…”
Section: Shigella Diversity: Epidemiology Geographical Distributionmentioning
confidence: 99%
“…Thus, further research is required to explore the transmission characteristics of Hubei Province. Numerous studies have indicated that Shigella consists of four species, namely dysenteriae, boydii, flexneri, and sonnei, among which the final two are the most common in low-and middle-income countries [36,43,44]. In our study, the dataset was obtained from routine infectious disease surveillance of the CDC in Hubei Province with no reported information regarding the Shigella species.…”
Section: Limitationsmentioning
confidence: 99%
“…The lack of data from Central Africa and from very low-income countries, such as CAR, 6 which suffers from long-term instability, highlights the need to improve our understanding of the spatial and temporal distribution of (sub-)serotypes in sub-Saharan Africa. 7,8 Central African Republic is a resource-limited country in equatorial Africa (ranked 180/187 according to the Human Development Index in 2013). Here, we describe the (sub-)serotype distribution and antimicrobial susceptibility of Shigella species isolated from patients in CAR during the 2002-2013 period.…”
Section: Introductionmentioning
confidence: 99%